The complete mitogenome of the freshwater crayfish Cherax cainii (Crustacea: Decapoda: Parastacidae). (2nd January 2016) - Austin, Christopher M.; Tan, Mun Hua; Croft, Laurence J.; Gan, Han Ming
Abstract: The complete mitochondrial genome of Cherax cainii was recovered from partial genome sequencing data using the HiSeq platform. The mitogenome consists of 15, 801 base pairs (69% A + T content) containing 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs and a 783 bp non-coding AT-rich region. This is the second completely sequenced mitogenome from the genus Cherax after the first reported Cherax destructor mitogenome nearly a decade ago.